Direct Radiative Effects of Sea Salt on the Regional Scale - Lundgren, Kristina (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2011)
This thesis aims to quantify the direct radiative effects of sea salt aerosol in the atmosphere. The online coupled regional scale model system COSMO-ART is extended for this objective with respect to the sea salt aerosol. Furthermore, a new sea salt optical parameterisation is developed for both the shortwave and longwave spectrum. Based on numerical simulations with the extended model system, the direct radiative effects of sea salt aerosol are investigated.